Crop farming: the use of pesticide and the law in Malaysia / Fara Zaila Abdullah, Lidia Fyrulliza Ishak and Nurakmal Farhan Aziz - Abdullah, Fara Zaila; Ishak, Lidia Fyrulliza; Aziz, Nurakmal Farhan (2008)
Sometimes foods carry small amounts of pesticides currently used on farms, and even pesticides no longer used, but which are long-lasting in the soil and water. Pesticide residues in research refer to the small amounts of pesticides and pesticide breakdown products in or on food. Pesticides need to be toxic to kill pests. However, a pesticide can be useful only if it kills pests at a small enough doses that causes little or no harm to people, domestic animals and wildlife. It is not easy to establish how much of a pesticide is "safe" for people. Despite many studies done on health effects of each pesticide, there are research gaps. These gaps cause uncertainty in the predictions of long-term health effects of many pesticides. It is thus essential that pesticide exposure be minimized and the presence of pesticide residues in food be regulated and monitored. Food safety is a key priority for the Government. It has an Executive Agency dedicated to the regulation of pesticides, the Pesticides Board to protect consumer interests in relation to food safety and standards. The procedure for approving pesticides for use in the Malaysia is rigorous and comprehensive and approval is only given if the pesticide has been shown to be safe to users, consumers and the environment. The aim of this project has been to go through the existing laws in Malaysia regarding the using, labeling and registration of pesticide and to come out with suggestion for appropriate amendments of the existing Pesticide Act 1974 and other regulations made under it relating directly to the usage of pesticides on crops inline to promote safe and healthy quality food. It is hoped that the research has been able to provide for better understanding and awareness regarding the pesticide and the law in Malaysia.